(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
An alternative form of tourism, festival tourism is dedicated to participating in celebrations and special events of any culture, region or nation. Trishul Jatra is a kind of local festival which stands out as a potential festival tourism product for its uniqueness, symbolic rituals and stories. As only few studies on the Jatra and festival tourism potential in the Nepalese context have been found during the present study, this study seeks to fill this gap by examining Trishul Jatra from tourism perspective based on a framework provided by previous studies. The study also identifies challenges that hindered the potential of Jatra as a tourism product. Conducting qualitative research with in-depth interviews and non-participant observation, the findings reveal five major issues that prevent the festival’s tourism potential including financial, socio-cultural, environmental, infrastructural and other issues. These findings provide practical implications to tourism stakeholders, government authorities and communities of the region for better planning, policymaking and sustainability of the festival.